Kewenangan Pengakuan Hak Pengelolaan Wilayah Laut Kepada Masyarakat Hukum Adat Oleh Pemerintah Daerah - Larubun, Faliuw Samuel; Nendissa, Renny Heronia; Matitaputty, Merlien Irene (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2023)
The state recognizes and respects the unity of customary law communities and their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia, which are regulated in law